Cultivar Susceptibility to Olive Knot Disease and Association with Endophytic Microbiota Community - Grazia Licciardello; Alexandros Mosca; Silvia Di Silvestro; Damiano Puglisi; Maria Patrizia Russo; Vittoria Catara; Paola Caruso (Agronomy, 2023)
Olive knot disease (OKD) induced by the bacterium Pseudomonas savastanoi pv. savastanoi seriously affects olive production in the Mediterranean basin. Nowadays, the only strategies to control the disease are pruning and the application of cupric products. An essential strategy to enhance protection is represented by the identification of resistant cultivars, which represents a crucial opportunity for future investments and breeding. We undertook a three-year-long survey at the International Olive Germplasm Collection of “Villa Zagaria” (Sicily, Italy) on thirty-six Sicilian cultivars that were monitored for symptom development. Cultivars with different levels of susceptibility were divided into five clusters. Moreover, in order to investigate possible interactions with endophytic microbial communities, two cultivars with contrasting susceptibilities, Zaituna (highly resistant) and Giarraffa (highly susceptible), were selected for an amplicon-based metagenomic analysis. Distinct endophytic communities colonized the two cultivars, suggesting an interaction between the resident bacterial community and the pathogen. Significantly higher bacterial richness was detected in the shoots of the susceptible cv. Giarraffa, although it had lower diversity. The opposite trend was observed for fungal communities. Among the microbes resulted to be enriched in cv. Giarraffa, it is important to underline the presence of Pseudomonas among the bacterial genera, and Alternaria, Neofusicoccum, Epicoccum, Ascochyta, and Elsinoe among the fungal genera, which include many species often described as plant pathogens and biocontrol agents. Starting from this basic information, new strategies of control, which include breeding for resistance and integrated disease management, can be envisaged.